Innovative Technologies for Producing Foam Concrete Products Using Solar Energy - Aruova, Lyazat; Dauzhanov, Nabi; Tokmyrza, Batyrkhan; Utkelbaeva, Aizhan; Shashpan, Zolaman (International Journal of Engineering and Technology, 2018)
An energy efficient technology and a method for the production of foam concrete products have been developed. They involve the use of solar energy in the process in order to reduce energy consumption for heat treatment, which allows to produce high-quality products with a low production cost with a daily production cycle.The technical and economic evaluation of the developed solar technology shows that during the hot season up to 95% of the heat energy needed to intensify the hardening of the foam concrete is provided by a renewable energy source. The annual replacement of organic fuels with solar energy, considering the winter period of the year, is up to 65%. The annual economic effect in the oil equivalent of the use of this solar technology in enterprises located in regions with favorable weather and climate conditions, with a productivity of 20 thousand m3/year is up to 85 tons.The use of solar technology to ensure accelerated hardening of foam concrete products makes it possible to make production highly efficient, energy-saving and environmentally friendly. It meets modern requirements for saving organic fuels and reducing harmful emissions into the atmosphere.The energy efficiency of a yearly solar thermal treatment consists of high heat-absorbing and heat-insulating ability of helio-coatings, helio-chambers, and controlling the expenses of the heat source. As a result, energy savings in the winter months are 15-35%, in summer - 70-100%, and the average annual energy savings are in the range from 50 to 75% depending on the class of concrete and the thickness of products.Â Â